2020
DOI: 10.1186/s12936-020-03492-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular forms of Anopheles subpictus and Anopheles sundaicus in the Indian subcontinent

Abstract: Background Anopheles subpictus and Anopheles sundaicus are closely related species, each comprising several sibling species. Ambiguities exist in the classification of these two nominal species and the specific status of members of these species complexes. Identifying fixed molecular forms and mapping their spatial distribution will help in resolving the taxonomic ambiguities and understanding their relative epidemiological significance. Methods DN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Instances exist where such intragenomic variations are overlooked and potentially inaccurate sequences are submitted to GenBank or documented in the research articles. A recent report by Sindhania et al [ 25 ] revealed that most of the ITS2-sequences of a molecular form of An . subpictus (prevalent mainly in Indian mainland, Form A) available in the public domain are incorrect due to the presence of indel in one haplotype that was unnoticed by the investigators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instances exist where such intragenomic variations are overlooked and potentially inaccurate sequences are submitted to GenBank or documented in the research articles. A recent report by Sindhania et al [ 25 ] revealed that most of the ITS2-sequences of a molecular form of An . subpictus (prevalent mainly in Indian mainland, Form A) available in the public domain are incorrect due to the presence of indel in one haplotype that was unnoticed by the investigators.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation has been documented in the case of An . subpictus (molecular Form A) where two ITS2 haplotypes were found present in all populations from northern India to Sri Lanka [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instances exist where such intragenomic variations are overlooked and potentially inaccurate sequences are submitted to GenBank or documented in the research articles. A recent report by Sindhania et al [22] revealed that most of the ITS2-sequences of a molecular form of An. subpictus (prevalent mainly in Indian mainland, Form A) available in the public domain are incorrect due to the presence of indel in one haplotype.…”
Section: Discussionmentioning
confidence: 99%
“…Such a phenomenon has recently been observed in the case of An. subpictus [22] and it was noted that all the reported intra-specific differences in a molecular form (Form A) of An. subpictus was in fact due to ambiguous DNA sequence chromatogram resulting from the presence of indel in one of the two haplotypes of ITS2 present in each individual.…”
Section: Introductionmentioning
confidence: 99%